Scouting Extracurricular Activities as a Means of Increasing Motivation for Physical Activity: an Analysis of Gender Differences in Students - Nadia Fadilla Damayanti; Agus Gumilar; Nuryadi; Burhan Hambali; Lusi Angelia (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Engaging students in physical activity through extracurricular programs remains a persistent challenge in educational settings, as declining participation rates continue to raise concerns among educators and health professionals. This study investigated the motivational factors underlying physical activity among Scouting extracurricular members at Kerinci 6 State Senior High School. A descriptive survey involving 40 participants (30 females, 10 males) measured both intrinsic and extrinsic motivation using a validated 28-item questionnaire with a reliability coefficient of 0.92.. Results indicated that male participants demonstrated marginally higher scores on both motivation dimensions compared to their female counterparts; statistical analysis, employing independent samples t tests, revealed no significant gender differences (p > 0.05). Correlation analysis yielded noteworthy findings: intrinsic motivation exhibited a near perfect correlation with physical activity motivation (r = 0.975, p < .001), substantially stronger than the correlation observed for extrinsic motivation (r = 0.797, p < .001). These findings suggest that fostering genuine interest and personal satisfaction prove more effective than external incentives in promoting sustained physical activity engagement. Longitudinal investigations are warranted to establish the durability of these motivational patterns.